Domestic Violence, Property and Family Law in Australia. (19th April 2018) - Easteal, Patricia; Young, Lisa; Carline, Anna
Abstract: In Australia, domestic violence has increasingly been recognized as germane to ancillary proceedings, including parenting and property matters. However, the road to recognition of the relevance of violence has been slow and the search for appropriate responses challenging. Drawing upon an explicitly feminist perspective, this article outlines the why and how of that relevance by looking at the ways in which family violence may intersect with family law property matters. We explain how a property settlement, both in process and outcome, may be either a manifestation of coercive control and/or affected by the legacy of coercive control. In terms of how this has been addressed to date, we chart the limited Australian responses and suggestions for reform, which have effectively left the judiciary to fashion a response with all the attendant difficulties of non-legislative reform. In conclusion, we maintain that the time is therefore ripe for a reconsideration of legislative – and other – responses to issues of family violence and property.